2006
DOI: 10.1007/s10194-006-0309-z
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of transcutaneous electrical nerve stimulation in chronic pain: short-term results of a double-blind, randomised, placebo-controlled trial

Abstract: The aim of this study was to test the efficacy of shortterm transcutaneous electrical nerve stimulation (TENS) treatment in chronic pain with respect to pain intensity and patients' satisfaction with treatment results. We therefore performed a randomised controlled trial comparing TENS and sham TENS. Patients, researchers and therapists were blinded for treatment allocation. One hundred and sixty-three patients with chronic pain referred to the Pain Centre entered the study. Conventional TENS and sham TENS wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…respectively for a mean duration daily, 5 times per week for 4 consecutive weeks (average of 20 treatment sessions) (18)(19)(20)(21).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…respectively for a mean duration daily, 5 times per week for 4 consecutive weeks (average of 20 treatment sessions) (18)(19)(20)(21).…”
Section: Methodsmentioning
confidence: 99%
“…TENS gel was applied on the surface of the electrodes to aid maximum transmission of current. Electrodes were placed on the skin overlying the painful area and held firmly in position as described by Radhakrishnan and Sluka (18); Oosterhof et al (19).…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4] The intensity of pain in cervicobrachial syndrome can reach severe or very severe levels, with symptomatic relief being the primary goal of physical therapies (cervical collar, kinesiotherapy, local heat application, vertebral manipulation) and pharmacologic treatment (nonsteroidal anti-inflammatory drugs, tramadol, systemic corticosteroids, anxiolytics, muscle relaxants, and opioids). Equivocal efficacy has been found with transcutaneous electrical stimulation, 5 infiltration of trigger points with local anesthesia 6 and acupuncture. 7 Variable efficacy has been demonstrated with physical treatments, and although pharmacologic treatment would appear to be a rational choice, it is not considered first-line, especially for chronic pain, because of the possible long-term side effects of some of the drugs.…”
mentioning
confidence: 98%
“…6 Moreover, high-frequency TENS affects the δ-opioid receptor and increases the levels of β-endorphins in the bloodstream and enkephalin in the cerebrospinal fluid. 10,27 With the possible exception of endogenous opiate release, the 'gate control theory' is in fact the most M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 14 tenable view. 2,12,16,21 This was advanced in 1965 by Melzack and Wall, who found that activation of non-noxious afferent Aβ fibers may inhibit the Aδ and C fibers that mediate nociceptive transmission.…”
Section: Discussionmentioning
confidence: 98%
“…However, no randomized controlled trial has yet been performed. 10,27 Hence, the principal aim of this study was to evaluate the efficacy and tolerability of tONS (compared with TPM) in migraine patients and to explore whether different tONS frequencies influenced treatment effectiveness.…”
Section: Introductionmentioning
confidence: 99%